Characterization and Antimicrobial Susceptibility of Pathogens Associated with Periodontal Abscess - Muhammad Irshad; Mohammad Khursheed Alam; Ahmad Alawneh; Mohammed Abdullah Alhadi; Ahmed Abdullah Alhadi; Yasser Saleh Almunajem; Fesal Farag Alanezi; Sharafi Abdullah Al Sagoor; Abdulrahman Mudaysh Bajawi; Ahmed Ali Alfawzan; Mohammad Amjad Kamal (MDPI AG, 2020)
Knowledge of microbial composition and antimicrobials' susceptibility to periodontal abscesses is vital for their successful treatment. The current study aims to provide a thorough overview of the clinical and microbial features of periodontal abscesses of the local community. The study was carried out at Rehman College of Dentistry, Peshawar, Pakistan between December 2019 to March 2020. Clinical measurements and microbial samples were collected from 45 subjects. Microbial samples were anaerobically cultured for the growth of selected bacterial species. E-test was used to assess the susceptibility of bacterial species grown from the patient samples to amoxicillin, azithromycin, metronidazole, and tetracycline. The majority of affected patients had preexisting chronic periodontitis. All abscesses clinically demonstrated bleeding on probing and suppuration. The periodontal abscess was most commonly associated with lower incisors and canines, followed by lower molars and then upper incisor and canine teeth. Fusobacterium spp. (73%) was the most frequently detected species followed by Prevotella intermedia/nigrescens (65%), Porphyromonas gingivalis (46%) and Aggregatibacter actinomycetemcomitans (24%). The detected clinical isolates of certain bacteria demonstrated resistance to all tested antibiotics except azithromycin. We conclude that Fusobacterium spp., P. intermedia/nigrescens, P. gingivalis, C. rectus, T. forsythia and A. actinomycetemcomitans are closely associated with periodontal abscess. Bacterial species associated with periodontal abscess demonstrated some level of antimicrobial resistance to amoxicillin, metronidazole and tetracycline while antibiotic resistance to azithromycin could not be demonstrated.